PERBANDINGAN EFEKTIVITAS INSOLE SEPATU DENGAN SUDUT 5° DAN 10° PADA PENDERITA DIABETES TIPE 2 - dwi purwantini; Ig. Heri Dwianto (coba, 2020)
Introduction: Physical activity can improve insulin sensitivity that leads to improve blood glucose control. The application of insole with a thicker design on the back of the shoe will create continues dynamic eccentric contraction. This study aims to compare the effectiveness between insoles of 5 ° and 10 ° to decrease fasting blood glucose levels (GDP) and blood glucose levels 2 hours postprandial (GDPP). Method: The research design used quasi-experimental study, with pre and post-test control design, subjects taken from type 2 diabetes mellitus in the Diabetes Association and Healthy Living in Surabaya as many as 19 people divided into two groups, one group wearing shoes with insole 5 ° for 5 days and second group wear shoes with insole 10 ° for 5 days. Blood samples were taken before and after wearing shoes with an insole. Data analyzed using Wilcoxon statistical test. Result: The results showed that fasting blood glucose levels in the shoe group with 5 ° insole had a p-value = 0.153 and the shoe group with 10 ° insole had a p-value = 0.011. While the blood glucose level 2 hours postprandial in the shoe group with 5 ° insole has a p-value = 0.139 and the shoe group with 10 ° insole has a p-value = 0.028. Discussion: The use of shoes with a 10 ° insole is more effective than the use of shoes with 5 ° insole.